Representações de letramento no contexto escolar: a construção de um conceito socialmente situado em um programa de formação de professores - Silva, Eliseu Alves da (2014)
Literacy has been the central point in researches and discussions in the field of Applied Linguistics (ROJO, 2010; SOARES, 2011), and the term is recurrently used in official documents, such as National Curriculum Parameters (BRASIL, 1997; 2000), National Curriculum Orientations (BRASIL, 2006), and recently, Lições do Rio Grande Curricular Referential (RIO GRANDE DO SUL, 2009). Considering this panorama, this work investigates the representations of elementary school teachers of Santa Maria, RS, about their concept of literacy and the way they represent discursively their classroom practices. The corpus was collected by using two questionnaires, answered, respectively, by 11 and 8 teachers that are participating in a continuing education program. Besides the questionnaires, we developed 14 reflexive sessions to problematize the concept of literacy. The analysis of the initial questionnaire showed three main concepts of literacy: as reading [critically] the world from everyday reality, as (de)coding the written language, and as a process of cognition and communication. According to the analysis of the participants discourse, in the classroom, these representations are materialized by pedagogical practices focused on contextualization, interpretation, thought expression, decoding and writing. The comparison of these data reveled contradictions between discourse and practices. Throughout the reflexive-collaborative process, during the reflexive sessions, these representations were reconfigured and expanded, including representations about literacy practices and events and, briefly, about relations between literacy and genres. Thus, the analysis of the final questionnaire demonstrated predominance of representations of literacy aligned to the concept of reading [critically] the world and timid upholds to the conception of literacy as a way of communication. Because of that, representations of pedagogical practices were also reconfigured and those practices identified in the initial questionnaire were reorganized into two categories: 1) appropriation of knowledge to life and 2) acquisition of technologies of writing. At the end of the reflective process we could delineate a socially situated concept of literacy as a process of social and political empowerment of the individuals which can help them transform reality the world (FREIRE, 1975) and, consequently, we observed re-significations in the teachers discourse about the way they see their own teaching practice.